Multi-Level Safety Studies of Anti Fel d 1 IgY Ingredient in Cat Food - Matulka, Ray A.; Thompson, Larry; Corley, David (Frontiers in Veterinary Science, 2020)
Chickens exposed to antigens produce IgY antibodies, similar in structure to mammalian IgG. Hens exposed with an allergen produced by cats (Fel d 1) results in production of anti-Fel d 1 specific IgY (AFD1), which is naturally concentrated in egg yolk. A chicken egg product ingredient containing AFD1 was evaluated for safety in a 26-week randomized, controlled, blinded tolerance study in cats and in vitro for mutagenic and genotoxic effects. The in vivo study was conducted with groups fed kibble containing 0, 7, 39, or 66 ppm AFD1. Parameters examined included: clinical observations, body weights, food consumption, serum chemistry, hematology, blood coagulation, urinalyses, and mortality and morbidity checks. AFD1 was evaluated for potential mutagenic effects utilizing the bacterial reverse mutation assay at concentrations of up to 2.78 ppm and for potential structural chromosomal aberrations at up to 3ppm using human peripheral blood lymphocytes. After 6-months of feeding to cats, there were no significant differences between control and any test groups in any parameters analyzed. No significant increases in mutations or chromosomal aberrations were observed in tests with or without S9. These studies show AFD1 was well-tolerated in cats at levels tested and does not induce mutagenic or chromosomal aberrations under study conditions.